Adaptive Light Control Berbasis Kendali Fuzzy - Noor Cholis Basjaruddin; Didin Saefudin; Richar Fredian; Kuspriyanto Kuspriyanto (Universitas Syiah Kuala, 2018)
Standard headlights will shine with a fixed intensity even though the environmental light changes. High-intensity lights sometimes make other drivers glare and potentially cause accidents. Adaptive Light Control (ALC) is a car headlights control system that can automatically adjust the intensity of the lamp according to the intensity of the light environment. In this research, we developed ALC which was able to regulate the intensity of the lamp according to the intensity of the environmental light including the light of the car in front. Light settings are performed using a fuzzy control system by utilising environmental light intensity and the distance of the car to the object as input. The developed ALC system was tested on remote control cars equipped with sensors and microcontrollers. The intensity of headlight begins to fade on the distance of the car to the object of 92 cm for objects in front of, 108 cm for objects on the left, and 22 cm for objects on the right.